2018
DOI: 10.35188/unu-wider/2018/530-5
|View full text |Cite
|
Sign up to set email alerts
|

Land rights, agricultural productivity, and deforestation in Vietnam

Abstract: This study has been prepared within the UNU-WIDER project on 'Structural transformation and inclusive growth in Vietnam'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Global policymakers are concerned about the possible effects of agricultural subsidies on the environment (Goodwin, 2011), yet there is limited empirical evidence in low and middle income countries. Estimates of the impact of agricultural policy on environmental outcomes can be divided into two categories: first, changes in crop type or demand for inputs, such as nitrogen fertilizer, that may harm the environment (Hendricks et al, 2014;Weber et al, 2016), and second, increases in agricultural productivity that may affect natural resources (Cohn et al, 2014;Assunção et al, 2017;Abman and Carney, 2020). Analyses focusing on input use and runoff externalities tend to find negative effects on water quality in high income settings, although some work shows that crop insurance can reduce chemical use (Smith and Goodwin, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global policymakers are concerned about the possible effects of agricultural subsidies on the environment (Goodwin, 2011), yet there is limited empirical evidence in low and middle income countries. Estimates of the impact of agricultural policy on environmental outcomes can be divided into two categories: first, changes in crop type or demand for inputs, such as nitrogen fertilizer, that may harm the environment (Hendricks et al, 2014;Weber et al, 2016), and second, increases in agricultural productivity that may affect natural resources (Cohn et al, 2014;Assunção et al, 2017;Abman and Carney, 2020). Analyses focusing on input use and runoff externalities tend to find negative effects on water quality in high income settings, although some work shows that crop insurance can reduce chemical use (Smith and Goodwin, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In this case the mechanism for conservation appears to be an increase in both agricultural productivity and income. Increases in agricultural productivity are also associated with decreased deforestation in Brazil (Assunção et al, 2017). However, analysis of the Green Revolution demonstrate conflicting effects for forests: Stevenson et al (2013) found that it saved land from being deforested and Foster and Rosenzweig (2003) that it increased deforestation.…”
Section: Introductionmentioning
confidence: 99%
“…This conjecture holds if there are no bidding constraints in factor or product markets limiting agricultural expansion. Existing literature generally refutes the Jevons Paradox, showing that agriculture extension programs aimed at small-scale agriculture in Malawi and Uganda (Abman and Carney, 2020;, or early electrification in Brazil (Szerman et al, 2022), reduced deforestation. An exception is Hess et al (2021), which found that community-driven development programs in Gambia increased deforestation.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have focused on the relation between 'illegal' logging and land tenure, poverty, and forest using-rights in Vietnam [14]. Some researchers have found the underlying causes of deforestation in the Mekong Region [15]; some researchers have studied the relationship between land tenure for small landholder agriculture and deforestation in Vietnam [16].…”
Section: Introductionmentioning
confidence: 99%